2006
DOI: 10.2307/30035537
|View full text |Cite
|
Sign up to set email alerts
|

How Should Middle-School Students with LD Approach Online Note Taking? A Mixed-Methods Study

Abstract: This explanatory sequential mixed-methods study explored how the encoding of text ideas is affected when students with learning disabilities (LD) take notes from Web-based text. In the quantitative phase of the study, 15 students took three kinds of notes - typed, copy and paste, and written - with each kind of notes addressing a different topic. After taking notes, students performed poorly on two immediate measures of facts learning. Cued-recall test performances were best for topics noted by writing, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The findings of the current study support findings of the three studies identified earlier. In the current study, highlighting and inserting comments to identify text elements alleviated some of the cognitive demands of writing, a finding similar to that of Igo et al (2006), whose investigation of methods for notetaking indicated that students with special needs preferred the copy and paste method because it was not laden with spelling, writing, or typing demands. While the highlighting and comment insertion was helpful as reported by the tutor, a preformatted digital scaffold, like the ones used by Englert, Wu, and Zhao (2005) and Englert et al (2007), might have increased students' planning time and facilitated a clearer line of reasoning throughout the essay, permitting the students to distribute the cognitive load.…”
Section: Benefits Of Online Environmentssupporting
confidence: 73%
“…The findings of the current study support findings of the three studies identified earlier. In the current study, highlighting and inserting comments to identify text elements alleviated some of the cognitive demands of writing, a finding similar to that of Igo et al (2006), whose investigation of methods for notetaking indicated that students with special needs preferred the copy and paste method because it was not laden with spelling, writing, or typing demands. While the highlighting and comment insertion was helpful as reported by the tutor, a preformatted digital scaffold, like the ones used by Englert, Wu, and Zhao (2005) and Englert et al (2007), might have increased students' planning time and facilitated a clearer line of reasoning throughout the essay, permitting the students to distribute the cognitive load.…”
Section: Benefits Of Online Environmentssupporting
confidence: 73%
“…Even if a strategy is belief consistent, enacted behavior may not parallel the belief. Despite a belief in the effectiveness of note-taking, many learners deliberately avoid note-taking, because the strategy is perceived as effortful and potentially promotes anxiety when lecture notes are spelled wrong or written incorrectly (Igo, Riccomini, Bruning, & Pope, 2006). Despite a belief in the effectiveness of note-taking, many learners deliberately avoid note-taking, because the strategy is perceived as effortful and potentially promotes anxiety when lecture notes are spelled wrong or written incorrectly (Igo, Riccomini, Bruning, & Pope, 2006).…”
Section: Identify Plausible Alternativesmentioning
confidence: 99%
“…CP note taking is a common student behavior (Igo et al, 2003;Igo et al, 2006). When students are instructed to take notes from the Web, the majority seems to prefer copying and pasting their notes to typing their notes.…”
Section: Why This Study Is Importantmentioning
confidence: 99%
“…When students are instructed to take notes from the Web, the majority seems to prefer copying and pasting their notes to typing their notes. In a mixed-methods study, 12 of 15 students with LD described CP to be vastly more appealing that both typing notes and writing notes from Web-based sources (Igo et al, 2006). Middle school students with learning disabilities (LD) seem to share this preference.…”
Section: Why This Study Is Importantmentioning
confidence: 99%
See 1 more Smart Citation